2019
DOI: 10.1098/rsta.2019.0105
|View full text |Cite
|
Sign up to set email alerts
|

Modelling strain localization in Ti–6Al–4V at high loading rate: a phenomenological approach

Abstract: A phenomenological approach, based on a combination of a damage mechanism and a crystal plasticity model, is proposed to model a process of strain localization in Ti–6AI–4V at a high strain rate of 10 3  s −1 . The proposed model is first calibrated employing a three-dimensional representative volume element model. The calibrated parameters are then employed to investigate the process of onset of stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…5). Zhou et al [28] reported that the whereas shear bands were present in significant numbers and spread over the sample when deformed at 800°C (Fig. 5).…”
Section: Effect Of Temperature On Mechanical Properties and Texturementioning
confidence: 96%
“…5). Zhou et al [28] reported that the whereas shear bands were present in significant numbers and spread over the sample when deformed at 800°C (Fig. 5).…”
Section: Effect Of Temperature On Mechanical Properties and Texturementioning
confidence: 96%